Penerapan Massage Kaki Kombinasi Relaksasi Napas Dalam terhadap Kecemasan pada Asuhan Keperawatan Pasien Hipertensi - Rantesigi, Nirva (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
This study aims to determine the Application of foot massage combined with deep breathing relaxation for anxiety in nursing care for hypertensive patients. The research method used is descriptive with a case study approach. The results showed that the pain scale was 6 (moderate), blood pressure 160/100 mmHg, pulse 110 x/minute, heart palpitations, and the patient said he was worried that the disease was getting worse, had difficulty sleeping and often woke up at night, anxiety score 21 (moderate), and the patient complained of difficulty moving his right hand, his condition was weak. His family helped him with his activities. Evaluation After carrying out nursing procedures for four days, the patient stated that the pain from the head to the nape of the neck had decreased, the patient looked relaxed, the pain scale was 3, the patient's blood pressure was 130/80 mmHg, the patient was calm, the patient slept soundly, the anxiety was reduced, and the anxiety scale was 13. Conclusion: The Application of foot massage combined with deep breathing relaxation can reduce stress in hypertensive patients. Keywords: Hypertension, Anxiety, Foot Massage, Deep Breathing Relaxation